Air Condition Monitoring Using Waypoint Based UAV (Unmanned Aerial Vehicle) - ahmad suroto; Achmad Ubaidillah (Universitas Trunojoyo Madura, 2018)
The lack of attention to the harmful gas such as karbonmonoksida (CO) and particulate matter (PM10) dust can give impact to the environment and living creatures that inhale it. With increasing industry the greater the level of air pollution. Monitoring the air condition industry is generally done by placing the sensor at certain points so inefficient and throwing out a lot of costs. Therefore it needs a tool that can monitor the State of the air in places hard that cannot be reached by a human being implemented on the Unmanned Aerial Vehicle (UAV). Unmanned Aerial Vehicle (UAV) or quadcopter is one of the types of aircraft used to fly and can move automatically in accordance with the navigation system based on compass and positioning of Global Positioning System (GPS) waypoint called so quadcopter can run automatically without the remote. The use of karbonmonoksida gas sensor (MQ-7) and sensor dust particles (GP2Y1010AU0F) can help quadcopter to automatic air condition monitoring. Testing the results of monitoring carried out by comparing the measuring tool on Dinas Lingkungan Hidup Provinsi Jawa Timur as a reference. The data generated from gas sensor MQ-7 and the dust sensor GP2Y1010AU0F emailed using telemetry 915 MHz are then processed on the PC/Laptop using fuzzy sugeno method to determine the output of air quality. The test results showed the average error monitoring for gas karbonmonoksida 3.31% and 8.47% of the dust particles. And a waypoint error of 2-5 meters.